Gender involvement in instrument playing: a case study of the Salvation Army brass band - Mutiza, Dorcas (Midlands State University, 2020)
The major purpose for this study was to examine gender involvement in instrument playing in The Salvation Army church Brass Band. The research employed a case study in the qualitative form. The four corps Nkulumane, Mpopoma, Bulawayo Citadel and Bulawayo temple were chosen as the case study because the researcher attends church services at one of the corps. Interviews, questionnaires and participant observation were used to collect data. Collected data was presented in the form of graphs and interpretation. Major findings of the study indicate that there is gender imbalance in the playing of instruments. This is so because of a number of factors that include stereotype, preferences lack of encouragement, limited time, incompetency and attitude towards the playing of brass instruments. Most females prefer to play the tambourine and hosho. It can therefore be recommended that The Salvation Army territorial council and corps councils encourage young girls to join the brass band so that they grow up with music knowledge and music background to organize and conduct workshops as well to help females to read and play music as this will help future generations.